POLICE MEASURES FOR COMBATING HOOLIGANISM AT SPORTING EVENTS - Veselinović, Jovan; Ivanović, Milan; Zenović, Filip; Stanojković, Sergej (Scientific Journal Management in Sports, 2015)
The subject of this paper refers to the suppression of increased aggressiveness and hooliganism at sporting events. The use of police force is successful if it is based on a thorough knowledge of local conditions and terrain, and also on quality information about the intentions of fans, strength and composition of the fan groups, as well as the forces that will join them or that support them, in case of an escalation of violence. Police organizations in different countries confront hooliganism at sporting events in different ways. At the beginning of supressing hooliganism, police forces primarily used repressive measures as the traditional model. When they later found that such measures did not bring adequate results, that in some situations they even encourage violence, they began to implement proactive measures. Obviously, repressive measures have not, nor will they ever be completely thrown out. Instead, they have been complemented by proactive measures in areas where there are no results, or where they are very poor. The objective of this paper is aimed at the fact that each sporting event is characterized by various factors - particular police units may be affected, others may not, but it is important that they are recognized. We used the method of analysis and synthesis.